Humoral Immunity and the Development of Obliterative Bronchiolitis after Lung Transplantation: Is There a Link? - Emtiazjoo, Amir M. (American Thoracic Society, 2013)
Lung transplantation is considered the definitive treatment for many end-stage lung diseases. However, the lung is rejected more commonly than other solid organ allografts. Obliterative bronchiolitis (OB) is the leading cause of chronic allograft dysfunction, and the key reason why the 5-year survival of lung transplant recipients is only 50%. The pathophysiology of OB is incompletely understood. Although a clear role for the immune response to donor antigens has been observed (also known as anti-human leukocyte antigens), evidence is emerging about the role of autoimmunity to self-antigens. This review highlights the current understanding of humoral immunity in the development of OB after lung transplantation.